PROBLEMS OF ENVIRONMENTAL POLLUTION DURING OIL REFINING - Associate Professor.1 Ruziyev. I. Kh; Mirzakobilov B. Yu.; Davronova B. Sh.; Sh. Rashidov (Web of Journals Publishing, 2025)
In this paper, the effects of oil and oil products on the ecosystem are considered, soil -contaminated with oil products, accidents, accompanied by the release or threat of the release of chemically hazardous substances (HOOV) as a result of explosions that lead to the destruction of technological networks and engineering structures. In addition, tasks in modern conditions are given that minimize undesirable consequences, rationally using natural conditions.
Keywords: Environmental pollution, oil refining, emissions of harmful substances, water and soil pollution, oil waste, atmospheric emissions, waste disposal, exposure to ecosystems, oil spills, and toxic compounds.